MEDICINAL PROPERTIES OF LAVENDER - LAVANDULA ANGUSTIFOLIA (Web of Teachers: Inderscience Research, 2025)
The article describes the medicinal properties and use of Lavender products for aromatherapy. Use of oils, above-ground parts of the plant. The biology of the plant is described.